Quantum aspects of beam physics - Joint ICFA Advanced Beam Dynamics and Advanced & Novel Accelerators Workshop (World Scientific, 2004)
"This was the third in the QABP workshop series"--Pref; Includes bibliographical references and index; This proceedings volume records the advances in quantum beam physics since the first meeting in Monterey (1998). In addition to further progress regarding quantum effects in beam dynamics, photon–electron interaction in beam handling, beam phenomena under strong fields, and quantum methodologies in beam physics, the newly introduced topics — the physics of condensed beams as well as astro-beam physics and laboratory astrophysics — have also been well documented by world experts in the field.